Community building through social media in a rural context. (10th November 2020) - Mishra, Gaurav; Shah, Reena
The proliferation of social media has transformed the interface between technology and interpersonal communication. In the rural context, there is scarce work done to understand the use of social media by farmers with the objective of community building. To address this gap, the current study endeavoured to gain insights into the WhatsApp community in the rural context formed to facilitate farming among the community members in developing country like India. In this study, an attempt has been made to understand how WhatsApp, as a platform for content generation and sharing, is used by a group of farmers located in remote villages of Gujarat, India. From the study, it is evident that the WhatsApp platform helped to share locally relevant, mainly, the farming related information. WhatsApp group has enabled the members to create their content, and therefore has given rise to a new information and communication ecosystem.